2020
DOI: 10.1016/j.cell.2020.03.045
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Basis of SARS-CoV-2 Entry by Using Human ACE2

Abstract: Highlights d SARS-CoV-2 interacts with hACE2 via S protein CTD d A 2.5-Å structure of SARS-CoV-2-CTD in complex with hACE2 is resolved d The SARS-CoV-2-CTD displays stronger affinity for hACE2 compared with SARS-RBD d SARS-CoV-2 -CTD is antigenically different from SARS-RBD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

104
3,380
0
41

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 2,801 publications
(3,525 citation statements)
references
References 57 publications
104
3,380
0
41
Order By: Relevance
“…Indeed, most of neutralizing monoclonal antibodies (mAbs) previously developed against SARS-CoV target the RBD epitopes, while a few are directed against the S2 subunit or the S1/S2 cleavage site ( 29, 30 ). The cross-reactivity of such mAbs with SARS-CoV-2 has been characterized, and it was found that many SARS-CoV-neutralizing mAbs exhibit no cross-neutralizing capacity ( 9, 31 ). For example, CR3022, a neutralizing antibody isolated from a convalescent SARS patient, cross-reacted with the RBD of SARS-CoV-2 but did not neutralize the virus ( 31, 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, most of neutralizing monoclonal antibodies (mAbs) previously developed against SARS-CoV target the RBD epitopes, while a few are directed against the S2 subunit or the S1/S2 cleavage site ( 29, 30 ). The cross-reactivity of such mAbs with SARS-CoV-2 has been characterized, and it was found that many SARS-CoV-neutralizing mAbs exhibit no cross-neutralizing capacity ( 9, 31 ). For example, CR3022, a neutralizing antibody isolated from a convalescent SARS patient, cross-reacted with the RBD of SARS-CoV-2 but did not neutralize the virus ( 31, 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed by biolayer interferometry studies that the receptorbinding domains of SARS-CoV-1 and SARS-CoV-2 S proteins bind with similar affinities to human ACE2 (19). In contrast, a modelling study suggested that binding of SARS-CoV-2 is stronger (20), which was convincingly confirmed by structural and biochemical data (16,17).…”
Section: Introductionmentioning
confidence: 83%
“…It cleaves both the SARS-CoV S protein and the virus receptor, ACE2, promoting both the viral uptake and the viral and cellular membrane fusion events (12)(13)(14). The critical residues contributing to the receptor-spike protein interaction were first determined for SARS-CoV-1 (15) and recently in three independent studies for SARS-CoV-2 (16)(17)(18). It has been proposed by biolayer interferometry studies that the receptorbinding domains of SARS-CoV-1 and SARS-CoV-2 S proteins bind with similar affinities to human ACE2 (19).…”
Section: Introductionmentioning
confidence: 99%
“…Once infection started, one monomer turned "up" its RBD to expose enough space to ACE2, inducing further conformational open and loose for proteolysis [1,3] . Atomic-level structural analysis suggested that the spatial interaction and interface between SARS-CoV-2 RBD and ACE2 was mostly in accordance with the SARS-CoV case [4] . Besides, a Cryo-EM structure of SARS-CoV-2 S protein trimer published recently showed that one of the three RBDs was in "up" conformation and naturally exposed the whole interaction interface [5] , while the classic closed symmetric trimer still existed [6] .…”
Section: Introductionmentioning
confidence: 83%
“…However, the real scenario is much more problematic. Several independent peer-reviewed studies as well as preprinted ones have proved that all structurally known SARS-CoV specific antibodies, including S230, 80R, m396 and F26G19, have no cross-reactivity of SARS-CoV-2 [4,5,9] . These antibodies all compete with ACE2 to bind SARS-CoV RBD, but their epitopes only have limited overlaps of the full ACE2-RBD interface, which could be the reason of lacking cross-reactivity.…”
Section: Discussionmentioning
confidence: 99%